Особливості зовнішньої політики урядового кабінету Народної партії Іспанії (2011–2014 рр.) - Матлай, Любава (Видавництво Львівської політехніки, 2015)
З’ясовано, що на зовнішню політику урядового кабінету правоцентристської Народної партії Іспанії негативно вплинула світова економічна криза, яка значно звузила міжнародну діяльність парламентської монархії. Розглянуто економічну дипломатію як пріоритетну в діяльності зовнішньополітичного відомства. The paper analyses the main features of Spain’s foreign policy and geostrategic priorities. It discusses the role of the changes that took place in the Spanish government in 2011. The author underlines the need for modernising the international priorities. It is emphasised that the financial crisis has a significant impact on the Spanish foreign policy. The Spanish government, headed by Prime Minister M. Rajoy, has initiated numerous reforms in an attempt to deal with the crisis. Spain’s foreign policy traditionally focuses on the European Union (EU), the Mediterranean and Latin America. In Spain the EU is regarded as a guarantor of Spanish democracy and economic development. Supporting the EU initiatives, Spain pays more attention to the national interests. The Europeanisation of Spain has two dimensions: the capacity for pursuing the Brussels policy at the domestic level and the ability to use its national preferences in the EU decision-making process. Unlike the previous governments of J. M. Aznar (1996–2004) and J. L. Rodriguez Zapatero (2004–2011), the current administration of M. Rajoy fully recognises the pivotal value of the European foreign policy coordination. The position that Spain defends in the EU is to «coordinate, coordinate and coordinate again». The Mediterranean remains important for the country’s foreign relations. Spain plays a crucial role in Latin America and it is second (behind the USA) when it comes to foreign aid in the region. The USA and Spain have long-standing relationships based on shared interests and values both at the bilateral and multilateral levels. Spain committed itself to defending global security, democratic values and human rights within a multilateral framework. This country is an excellent partner at the multilateral level and it successfully cooperates with the United Nations (UN), the North Atlantic Treaty Organization (NATO), the Organization for Security and Cooperation in Europe (OSCE) and other institutions.
The foreign policy features of the Spanish People’s Party government (2011–2014)
Keywords: Іспанія; зовнішня політика; економічна криза; Народна партія; Маріано Рахой; Європейський Союз; міжнародна співпраця; Spain; foreign policy; economic crisis; People’s party; Mariano Rajoy; the European Union; international cooperation